Employee Engagement, Budaya Organisasi dan Loyalitas Pegawai terhadap Kualitas Pelayanan PublikK - Wiwik Diana Farida; Muhlis Hafel; Andi Wijaya (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
The aim of this research is to find out and test whether there is an influence of employee engagement, organizational culture and employee loyalty together on the quality of public services at the Manokwari Class I Correctional Center. This research uses a quantitative approach because it is objective in testing hypotheses. This research was carried out at the Manokwari Class I Correctional Center. Data collection techniques include observation, interviews and questionnaires using descriptive statistical data analysis techniques. The research results show that employee engagement, organizational culture and employee loyalty have a very strong and significant influence on the quality of public services at the Manokwari Class I Correctional Center. In conclusion, team member engagement, organizational culture, and team member loyalty influence the quality of public services at the Manokwari Class I Correctional Center. Keywords: Employee Engagement, Employee Loyalty, Organizational Culture.